Dampak Internet Terhadap Akses Informasi Bisnis Dan Kontribusinya Terhadap Kinerja Bisnis - Agit, Alamsyah; Muharram, Susilawati; Oktavianty (Sehati Abdimas, 2023)
The internet is a necessity in modern times, the ease of internet access makes it easier to access knowledge, information and various media faster. Thus, every individual has the capability to develop skills and expertise. Not limited to a certain context, the internet helps provide a lot of information, including business information. This information certainly has a contribution to business performance. Based on this phenomenon, this research aims to determine the extent to which the internet can support business performance through the wide availability of business information. This research uses a qualitative approach, data collection is carried out by interviews, the data analysis technique used is deductive reasoning to group data and interpret and formulate the results and conclusions of this research. The results of this research show that most of the internet is used to find business inspiration and various new business methods that are more cost-effective. However, much of the increase in business is due to the internet providing various information that shows product trends that are selling well in the market, so that business owners can sell similar products, or alternative products with the same function. Apart from that, the internet also provides various investment information, and several platforms for making online sales, or doing side jobs that can increase business owners' income